ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI PEMBAGIAN PADA PESERTA DIDIK KELAS V DI SD NEGERI PRIGI 1 KABUPATEN BOJONEGORO - Lestari, Dwi Putri; Pratikno, Ahmad Sudi (LPPM STAI Muhammadiyah Probolinggo, 2024)
The learning abilities of each student are not all the same, but their abilities are different. Many students still have difficulty understanding the material and working on the questions that have been given. The most common learning difficulties experienced by students are in mathematics lessons. The aim of this research was to find out what learning difficulties experienced by class V students at SD Negeri Prigi 1 Kanor in the distribution material and what factors influenced it. This research uses a descriptive qualitative method with triangulation data collection techniques, namely through interviews, observation and documentation. The results of the research that has been carried out show that difficulties in learning mathematics for class V students regarding division are difficulties in understanding the concept (difficulty using counting skills in a downward order), difficulty in subtracting numbers, difficulty working on story-based questions, and difficulty in writing down values. place. Meanwhile, the factors that cause their learning difficulties consist of internal factors including the lack of enthusiasm and enthusiasm of students when learning takes place and external factors which include the use of monotonous learning methods such as the lecture method, no supporting learning media, and lack of parental support in learning mathematics.